2018
DOI: 10.1097/jte.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Using a Valid and Reliable Measure to Assess Clinical Instructor Self-perception of Teaching Behaviors

Abstract: Introduction. The purpose of this study was to 1) use the Clinical Teaching Effectiveness Questionnaire (CTEQ) to determine the self-perception of clinical teaching effectiveness (CTE) with a current sample of clinical instructors (CIs) and 2) determine if a relationship exists between CI characteristics and self-perceived ratings. Methods. A cross-sectional study was completed with a convenience sample of 194 physical therapists who served as CIs for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Earlier research did not consistently demonstrate a relationship between the highest degree earned and CTE. 6 Wetherbee et al 9 and Morren et al 10 found no significant relationship between highest degree earned and CTE, whereas Buccieri et al 25 and Wormley et al 15 did find a positive relationship between highest degree earned and CTE. Several previous studies examining ABPTS certification and CTE found no relationship.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Earlier research did not consistently demonstrate a relationship between the highest degree earned and CTE. 6 Wetherbee et al 9 and Morren et al 10 found no significant relationship between highest degree earned and CTE, whereas Buccieri et al 25 and Wormley et al 15 did find a positive relationship between highest degree earned and CTE. Several previous studies examining ABPTS certification and CTE found no relationship.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Despite their intrinsic benefits, all tools have drawbacks such as reliance on a single perspective and a lack of specificity to contemporary teaching strategies. [21][22][23] Additionally, no data exist detailing how frequently these tools are utilized, which makes it difficult to determine how consistently CIs are assessed or provided with feedback. The tool most referenced in clinical settings is the APTA Physical Therapist Student Evaluation: Clinical Experience and Clinical Instruction (PTSE).…”
Section: Current Status: Defining and Assessing Excellence In Clinical Teachingmentioning
confidence: 99%
“…The most contemporary tool is the Clinical Teaching Effectiveness Questionnaire (CTEQ). 23 Developed by Wormley et al, 23 the CTEQ is a validated self-reflection tool for CIs. Self-reflection is an important mechanism in the development of skill and expertise, but there can be concerns related to the accuracy of rating in such tools; high achievers tend to underrate performance and low achievers tend to overrate performance.…”
Section: Current Status: Defining and Assessing Excellence In Clinical Teachingmentioning
confidence: 99%
“…This effort provided the foundational content for clinical instructor training and assessment in physical therapy clinical education. Researchers and educators have since identified similar clinical instructor characteristics and categories, while also noting the importance of supervisory skills and environmental support of clinical instruction(Newstead, Johnston, Nisbet, McAllister,2017;Wormley, Romney, & Greer, 2018; Recker-Hughes,Wetherbee, Buccieri, Fitzpatrick Timmerberg & Stolfi, 2014;Bridges, et al, 2013;Kelly, 2007; American Physical Therapy Association, 2004; American Physical Therapy Association, 2003) (Wormley et al, 2018;Recker Hughes et al, 2010;Buccieri et al, 2006). vantage points.…”
mentioning
confidence: 99%
“…not regularly assessed. More recently,Wormley et al (2018) studied CI perspectives using the Clinical Teaching Effectiveness Questionnaire(Wormley, Romney, & Greer, 2017) and its 30 CI characteristics in the categories of Learning Experience, Learning Environment, Communication, and Evaluation. They found that, overall, clinical instructors rated themselves as effective in each category of clinical teaching.…”
mentioning
confidence: 99%